Predicting Social Anxiety and Subjective Well-Being Preservice Teachers through Doing Sports - Samar, Ezgi; Çalık, Fehmi; Yaşar, Emin; Ece, Cuma; Şen, Murat; Şen, Betül; Bilir, Mihrab (Asian Journal of Education and Training, 2019)
In the study, it is aimed to research the social anxiety and subjective well-being of preservice teachers through doing sports. A total of 450 pre-service teachers majoring in various teaching areas including science Turkish, English, Elementary Mathematics and Primary School teaching at a state university in the Southeastern Anatolia Region participated in the study. The data were collected via a Personal Information Form, Social Anxiety Scale, and Subjective Well-Being Scale. T-test and analysis of variance (ANOVA) were used when compared the independent groups, Tukey’s test was used for comparison of differences. The Pearson correlation test was tested for the relation between continuous data. When based on gender, the scores of female participants of social anxiety and value lessness are significantly different. When based on age, subjective well-being scores of 23 years and older participants are significantly high. Generally, subjective well-being scores of pre-service teachers who do sports are significantly high while their value lessness scores are significantly low. In the comparison of participants at the age of 23 and younger with reference to doing sports, subjective well-being scores of participants doing sports was significantly higher than those of the ones not doing sports. However, it was detected that their scores of social anxiety, social aversion and being criticized did not differ significantly with reference to doing sports. It was detected that there was no significant difference in comparison of scores subjective well-being, social anxiety, social aversion, value lessness and being criticized belonging to participants at the age of 24 and older with reference to doing sports. In this study, found that subjective well-being scores of those who did not do sports were lower than those who did sports. In addition, it has been determined that the total points of social avoidance, worthlessness and social anxiety do not differ among those who do sports and do not.